Molecular and biological characterization of Cowpea Mild Mottle Virus (CPMMV) isolates infecting soybean in Bali and its host range - GUSTI NGURAH ALIT SUSANTA WIRYA; LISTIHANI LISTIHANI; DEWA GEDE WIRYANGGA SELANGGA; TRISNA AGUNG PHABIOLA; I GEDE RAI MAYA TEMAJA; NI NYOMAN SISTA JAYASANTI; I PUTU BAWA ARIYANTA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Wirya GNAS, Listihani L, Selangga DGW, Phabiola TA, Temaja IGRM, Jayasanti NNS, Ariyanta IPB. 2026. Molecular and biological characterization of Cowpea Mild Mottle Virus (CPMMV) isolates infecting soybean in Bali and its host range. Biodiversitas 27 (4): d270441. https://doi.org/10.13057/biodiv/d270441. Cowpea Mild Mottle Virus (CPMMV) is one of the main pathogens infecting soybean (Glycine max), characterized by mosaic symptoms on young leaves. The host range of CPMMV in Indonesia remains unclear, and there have been no reports of it in Bali soybean plants. This research aims to analyze the CPMMV spread in soybean plants in Bali and to test the CPMMV host range on several plants from Fabaceae, Solanaceae, Amaranthaceae, and Chenopodiaceae. This study was carried out by surveying and sampling symptomatic soybean plants from nine regencies in Bali. Samples obtained from this study were 270 symptomatic soybeans. The samples were then used for CPMMV detection via RT-PCR, CP gene cloning, sequencing analysis, and host range test on 11 test species. The CPMMV infection in soybean resulted in mosaic symptoms, leaf malformations, and stunting. The percentage of symptomatic soybean samples testing positive for CPMMV in nine regencies in Bali ranged from 23.08% to 92.37%. DNA cloning was successfully conducted, as indicated by the ±958 bp insert gene in the plasmid recombinant. The CPMMV isolate from Indonesia has the closest homology with Taiwan and Chinese isolates (93.38-95.71%). Of the 11 test plants, Chenopodium giganteum and Gomphrena globosa showed local symptoms, while the other nine showed systemic symptoms. After reverse inoculation on soybean, all test plants exhibiting systemic symptoms were suitable as sources of CPMMV inoculum. Therefore, the Bali CPMMV isolate may serve as a host and an inoculum source for soybeans. Thus, these results are necessary for intercropping practices involving soybean cultivation.